The Euroschool Lectures on Physics with Exotic Beams, Vol. III - Al-Khalili, J.S; Roeckl, Ernst (Lecture Notes in Physics, 2009)
This is the third volume in a series of Lecture Notes based on the highly successful Euro Summer School on Exotic Beams. The aim of these notes is to provide a thorough introduction to radioactive ion-beam physics at the level of graduate students and young postdocs starting out in the field. Each volume covers a range of topics from nuclear theory to experiment and applications. Vol I has been published as LNP 651, ISBN 978-3-540-22399-3; Vol II has been published as LNP 700, ISBN 978-3-540-33786-7.